The Urgency of Parental Parenting Patterns in Shaping the Morality of Middle School Students - Wasito, Wasito (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
It is interesting to study students at Kepung Islamic Middle School in the moral aspects of habblum minallah, habblum minannas and habblum minal alam. Of all the students who have carried out good morals, 1 out of 5 people. This is closely related to the upbringing of parents for their children. Every form of authoritarian, democratic or parmissive parenting used by parents will determine the morals of a child. This is what is interesting for the authors to conduct research on students at Kepung Islamic Middle School. The author observes that the students of this school come from different geographic areas, some come from the mountains, come from 3 different districts and they are asked to help their parents with their work. In this study used a type of qualitative research, with a descriptive approach. The results of the study are: 1) The role of parenting is carried out by a father and mother, both of whom complement each other and work together in providing parenting to their children. 2) The parenting style used by parents uses authoritarian, democratic and permissive forms, each of which has its own advantages and disadvantages to the child's morals. 3) The results of parenting parents, according to the school, some children have been able to apply good morals to Allah SWT, teachers, parents, friends and their environment.